2019
DOI: 10.1017/wet.2018.121
|View full text |Cite
|
Sign up to set email alerts
|

Off-target Movement of DGA and BAPMA Dicamba to Sensitive Soybean

Abstract: It is well established that dicamba can cause severe injury to soybean that is not resistant to dicamba. Dicamba-resistant (DR) cotton became available in 2015, followed by DR soybean in 2016; in late 2016 came the release of new dicamba formulations approved for topical use in cotton and soybeans. Until this approval, use of dicamba was limited to primarily corn, small grains, range and pasture, and eco-fallow acres. Hence, studies were conducted in 2015 and 2016 to examine off-target movement of two dicamba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 23 publications
0
57
0
Order By: Relevance
“…Volatility of these new formulations, which have been shown to be less volatile than older dicamba formulations in extensive humidome research, has remained a point of concern (Long et al, 2016: Mueller, 2015). Recent studies of sensitive soybean plants placed in the field 30 min after dicamba applications has indicated that both formulations can volatilize in the field setting (Jones et al, 2019). Air sampling data from this study provide additional support for the ability of each formulation to volatilize in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Volatility of these new formulations, which have been shown to be less volatile than older dicamba formulations in extensive humidome research, has remained a point of concern (Long et al, 2016: Mueller, 2015). Recent studies of sensitive soybean plants placed in the field 30 min after dicamba applications has indicated that both formulations can volatilize in the field setting (Jones et al, 2019). Air sampling data from this study provide additional support for the ability of each formulation to volatilize in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The tarp at this site was rested on the plants to ensure no risk for physical drift. In Arkansas, 19-L buckets covering three non-DR soybean plants were used similar to that used in other dicamba research (Jones et al 2019). Plant injury ratings were collected at 28 d after application (DAA) in Wisconsin and 21 DAA at all other sites.…”
Section: Plant Effectsmentioning
confidence: 99%
“…To further reduce injury to sensitive plants due to OTM of dicamba, numerous restrictions have been added to the dicamba labels, including nozzle type, approved mixtures, exclusion of ammonium sulfate, carrier volume, boom height, application speed, wind speed and direction, and buffer zones. Research in Arkansas, Missouri, Tennessee, Nebraska, and Indiana has reported that under certain environmental conditions, these new formulations of dicamba can still volatilize and move to nontarget areas, even when applied according to the manufacturers' recommendations (Jones et al 2019;Norsworthy et al 2018). A national survey conducted by the University of Missouri in 2017 reported soybean injury on 1.3 million ha in the United States (Bradley 2017).…”
mentioning
confidence: 99%
“…Spray drift is the part of the pesticide application deflected away from the target area during or following applications 5 . Glyphosate, 2,4-D, and dicamba spray drift have been reported to cause severe injury on sensitive vegetation and crops, especially when best practices are not adopted during applications [6][7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%